Kajian Aktivitas Infeksi Rhizobium sp. Indigenus Pada Kerandang (Pueraria phaseoloides) - Triwahyuningsih, Nike; Pristiwantoro, Eko Cahyo; Utari, Lilik (Universitas Muhammadiyah Yogyakarta, 2005)
Kudzu, a kind of legume cover crops (LCC), plays important roles in soil and water conservation. It is effective for inhibiting erotion, compaction and leaching of nutrients, as well as to suppress weeds. Plants growing with legume ground covers usually show better nutrition, growth and yield. Recently, this cover crops have been widely used to prevent the negative effects and to improve soil physical and nutritional characteristics. As a legume, bacterial inoculation is to enhance the infection and nodulation activity. A research to observe the role of indigenous Rhizobium on infection and nodulation activity of kudzu was carried out in September till December 2004. The research was done in Regosol volcanic soil in Tlatar Village of Sawangan in Magelang district of Central Java. A pot experiment was arranged in 4x2 factorial completely randomized design which was repeated three times. The seedling innoculation with root nodules endophytic bacteria was to increase nodulation and to enhance Kudzu plant growth. The seedlings were inoculated with 1, 2 and 3 ml/pot of grinded root nodules of wild plants containing endophytic Rhizobium sp. The wild kudzu plants were taken from coastal sandy land of southern Yogyakarta. All treated seedlings were planted in a sterilized medium to be compared to the unsterilized one in order to examine the role of indigenous bacterias. Observation on bacterial infection activity, nodulation, and plant growth were taken at week 4, 6, 8, and 10. All the datas were variance analyzed and the treatments average were tested with 5% level of Duncan's multiple range test. The results showed that application of 2 ml/pot of innoculum significantly increased the infection activity, nodulation and plant growth. Sterilized soil decreased the infection activity. Since the innoculation of endophytic Rhizobium sp. in unsterilized soil significantly increased the infection actifity, nodulation and plant growth, so the indigenous Rhizobium sp. in rhizhosfer was needed to sinergisticaly worked well with inoculum to increase infection activities and root nodulation.